Plantas medicinais e tecnologias sociais para o desenvolvimento local na Amazônia: a experiência do estado do Amapá - SOUZA, Armando Eduardo de (Universidade Federal do Pará, 2018)
This paper aims to point out the social, economic and environmental influences of Medicinal Plants and Herbal Medicine, while Social Technologies, to local development in the Amazon from local experiences of the Amapá State. The hypothesis of the research is based on the premise that the Medicinal Plants and Herbal Medicine not only contribute to the solution of problems related to health, but also improve the economic, social and environmental conditions of local communities in the Amazon. In the pharmaceutical industry, technological advancement has achieved good results in the prevention and treatment of various diseases contributing to the reduction of problems related to health in many countries, on the other hand, some local communities are not getting all the benefits from advances in pharmaceutical industry . In this sense, the World Health Organization has encouraged countries to develop public policies to the use of traditional medicine and other traditional practices in health as a treatment option in the public system. The experiences observed in the use of medicinal plants in Brazil and the world, justifying its importance in both social and in the economic and environmental aspects. The site survey are two institutions that provide services related to herbal medicine and medicinal plants in the state of Amapá. This is an exploratory study, developed through bibliographical and documentary research, complemented with interviews with people who have experienced social technologies. The results showed that these institutions have achieved good results in solving problems related to health, perfecting Phytotherapy with greater access to treatment to users of primary care services to health and encouraging social participation in finding solutions to local health problems. It was concluded that social technologies with medicinal plants can be easily replicated in other communities, contributing to the foundation of local development in the Amazon.